2008
DOI: 10.15388/informatica.2008.229
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Alignment Templates Induction

Abstract: This paper examins approaches for translation between English and morphology-rich languages. Experiment with English-Russian and English-Lithuanian revels that "pure" statistical approaches on 10 million word corpus gives unsatisfactory translation. Then, several Web-available linguistic resources are suggested for translation. Syntax parsers, bilingual and semantic dictionaries, bilingual parallel corpus and monolingualWeb-based corpus are integrated in one comprehensive statistical model. Multi-abstraction l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…These models can robustly perform alignments on the bilingual corpus which usually represents a technical (literal) translation. But when we use a corpus of fiction books, these algorithms frequently give sparse and erroneous alignments (Laukaitis & Vasilecas, 2008;Laukaitis et al, 2011).…”
Section: Related Workmentioning
confidence: 99%
“…These models can robustly perform alignments on the bilingual corpus which usually represents a technical (literal) translation. But when we use a corpus of fiction books, these algorithms frequently give sparse and erroneous alignments (Laukaitis & Vasilecas, 2008;Laukaitis et al, 2011).…”
Section: Related Workmentioning
confidence: 99%
“…Nevertheless, we found that precision and recall of existing algorithms are too low in order to consider them practical when it comes to an alignment of translated fiction books. As shown in Laukaitis and Vasilecas (2008), Laukaitis et al (2011), the accuracy of these methods decreases drastically when we try to align a text that contains discrepancies, e.g. some book page layout segmentation strings, missing sentences and frequent one-to-many alignments.…”
Section: Related Workmentioning
confidence: 99%
“…Similar problem is studied by (Paradauskas, Laurikaitis 2006) were they analysed the process of enterprise knowledge extraction from relational database and source code of legacy information systems. (Laukaitis, Vasilecas 2008) presented a system that leverages extracted information from an online linguistic resource (Wordnet 10 ) to induce syntactic and semantic transformation rules. These rules are then used to improve machine learning based language translation.…”
Section: Research On Data Extraction In Lithuaniamentioning
confidence: 99%